2010
DOI: 10.3109/01612840.2010.488784
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health Nurse Incentive Program: The Benefits from a Client Perspective

Abstract: It is now acknowledged that a substantial proportion of the Australian population will experience a mental health condition at some time during their lives. Only a small proportion will access care and treatment for these conditions, and those who do are more likely to access general medical practitioners than specialist mental health providers. The Mental Health Nurse Incentive Program (MHNIP) was introduced by the Commonwealth Government to enhance access to mental health care by engaging mental health nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 54 publications
(36 reference statements)
2
25
0
Order By: Relevance
“…() study, which identified the centrality of effective communication to the therapeutic relationship. Research indicates that consumers are seeking more meaningful interactions with MHNs, including “friendship” based relationships, and suggest that MHNs should do more “ordinary things” with consumers to help build positive social relationships, that this “ordinariness” helps to demonstrate a “caring about”, rather than “caring for” approach (Happell & Palmer, ). Several participants in this study also identified “friendship” with their MHN as contributing positively to QOL.…”
Section: Discussionmentioning
confidence: 99%
“…() study, which identified the centrality of effective communication to the therapeutic relationship. Research indicates that consumers are seeking more meaningful interactions with MHNs, including “friendship” based relationships, and suggest that MHNs should do more “ordinary things” with consumers to help build positive social relationships, that this “ordinariness” helps to demonstrate a “caring about”, rather than “caring for” approach (Happell & Palmer, ). Several participants in this study also identified “friendship” with their MHN as contributing positively to QOL.…”
Section: Discussionmentioning
confidence: 99%
“…These initiatives also demonstrate that when provided with access to education and training and the ability to work collaboratively with primary health care professionals, MHNs integrate physical and mental health needs and are capable of providing high standards of physical health care to people with SMI (Happell & Palmer, 2010;Happell, Palmer, & Tennent, 2011). Similarly incorporation of a nurse practitioner into mental health multidisciplinary teams to provide physical health assessments may result in improved health outcomes for this group (Unutzer et al, 2006).…”
Section: Collaboration Among Primary and Secondary Care And People Wimentioning
confidence: 92%
“…Similarly, GPs acknowledge that they don't have the confidence or specialist skills to treat people with a mental illness (Bitar, Springer, Gee, Graaf, & Schydlower, 2009) and that they have no time to provide physical care to this group (Lawrence & Kisley, 2010). This perception is shared by consumers who believe that medical practitioners do not have adequate training in mental health (Happell & Palmer, 2010).…”
Section: Lack Of Education and Training For Health Care Professionalsmentioning
confidence: 96%
“…The young people became involved in the art group via referral by Headspace practitioners, including those under the mental health nurse incentive programme that funds credentialed mental health nursing interventions for those with serious mental illnesses (Happell & Palmer 2010). The service runs a weekly social recovery project during the school term (the art group) attended by approximately 15 Headspace consumers, both male and female.…”
Section: Methodsmentioning
confidence: 99%